Symposium 7: Learning Cultures in Online Education: Symposium Introduction - Goodfellow, Robin (Proceedings of the International Conference on Networked Learning, 2008)
The papers in this symposium are based on contributions to an edited collection of work that addresses the theme of ’learning cultures in online education’, to be published by Continuum books later this year (Goodfellow & Lamy in preparation). Research on online learning cultures is an important corollary to the use of e-learning to develop ’transnational’ and ’cross-border’ education markets if the social and pedagogical benefits from these developments are to keep pace with the corporate and institutional ones, but it is also a corollary to the teaching of the increasingly diverse learner cohorts that inhabit formal online learning communities, and to the increasingly blurred distinction between these learning communities and the more informal ones that are appearing in a variety of sites of online social networking. The work collected in the book addresses issues such as the continuing relevance of a conceptualisation of culture that equates it with national identity and locates it in the behaviour of individual learners, the processes through which identities and value systems are negotiated amongst individual and institutional actors in virtual learning environments, the complex role of technologies themselves as cultural actors, and the relationship between formal educational and popular media cultures. The three papers in this symposium address: the nature of research into culture in online learning to date, and the new directions proposed in the forthcoming book; the role of ritualised and textualised language in the construction and presentation of identities online; and the influence of the ’behaviour’ of technical environments on the cultural ecology of online learning communities.